1976
DOI: 10.1093/bja/48.12.1197
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Doxapram on Postoperative Pulmonary Function in Patients Undergoing Upper Abdominal Surgery

Abstract: An infusion of doxapram 250 mg in dextrose 5% compared with dextrose 5% alone in patients recovering from upper abdominal surgery was associated with a reduction in the degree of hypoxaemia after operation. This may be the result of a sparing effect on the functional residual capacity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1977
1977
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Numerous animal and human studies in the 1970s confirmed that doxapram improves arousal and level of consciousness following anesthesia induced by barbiturates, volatile anesthetics, nitrous oxide and benzodiazepines. A doxapram infusion improved oxygenation and reduced the incidence of pulmonary complications in patients recovering from upper and lower abdominal surgery (14,19,30). Doxapram also increased arousal and shortened recovery time in patients having outpatient surgery (44).…”
Section: Post-anesthesiamentioning
confidence: 99%
“…Numerous animal and human studies in the 1970s confirmed that doxapram improves arousal and level of consciousness following anesthesia induced by barbiturates, volatile anesthetics, nitrous oxide and benzodiazepines. A doxapram infusion improved oxygenation and reduced the incidence of pulmonary complications in patients recovering from upper and lower abdominal surgery (14,19,30). Doxapram also increased arousal and shortened recovery time in patients having outpatient surgery (44).…”
Section: Post-anesthesiamentioning
confidence: 99%
“…In these subjects changing the ventilatory pattern from IPPV to CPPV improved arterial oxygenation but was not associated with nitrogen release from areas where airways might have been re-opened. Another factor may be the size of tidal volumes, since treatment with a respiratory stimulant (doxapram) increases tidal volume and reduces hypoxaemia (Winnie et al, 1971;Lees et al, 1976;Pflug et al, 1976).…”
Section: Discussionmentioning
confidence: 99%
“…Doxapram hydrochloride is a respiratory stimulant which has an action both centrally and on the peripheral chemoreceptors (Kato and Buckley, 1964;Wang and Hirsch, 1973;Scott, Whitwam and Chakrabarti, 1977). The administration of doxapram has been shown to reduce respiratory complications and hypoxaemia in fit patients after abdominal surgery (Gupta and Dundee, 1974;Gawley, Dundee and Jones, 1975;Gawley et al, 1976;Downing et al, 1977).…”
mentioning
confidence: 99%